2020
DOI: 10.1177/2332858420901496
|View full text |Cite
|
Sign up to set email alerts
|

Connections and Capacity: An Exploration of Preservice Teachers’ Sense of Belonging, Social Networks, and Self-Efficacy in Three Teacher Education Programs

Abstract: Learning to teach is rife with challenges. Preservice teachers’ self-efficacy can potentially mitigate the stress of these challenges, and teacher education programs are fundamental in helping them build this important resource. As such, understanding the foundations of self-efficacy is important for researchers and teacher educators alike. Grounding our study in social network theory, we explored the relationship between sense of belonging to a teacher education program, network centrality, and self-efficacy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 113 publications
0
23
0
3
Order By: Relevance
“…One of the main goals of this paper is therefore to address this gap in the literature. Bjorklund et al (2020) found that a sense of belonging can give preservice teachers a space where they feel confident to grow and develop as teachers and increase feelings of teacher self-efficacy; we theorize that sense of belonging within a teacher education program will also be related to feelings of SWB for preservice teachers.…”
Section: Sense Of Belongingmentioning
confidence: 77%
See 4 more Smart Citations
“…One of the main goals of this paper is therefore to address this gap in the literature. Bjorklund et al (2020) found that a sense of belonging can give preservice teachers a space where they feel confident to grow and develop as teachers and increase feelings of teacher self-efficacy; we theorize that sense of belonging within a teacher education program will also be related to feelings of SWB for preservice teachers.…”
Section: Sense Of Belongingmentioning
confidence: 77%
“…Despite the growing research and positive outcomes related to sense of belonging in undergraduate settings, there is a dearth of research on the topic in postgraduate settings, such as teacher education programs (e.g., Bjorklund et al, 2020;Bjorklund and Daly, 2021). One of the main goals of this paper is therefore to address this gap in the literature.…”
Section: Sense Of Belongingmentioning
confidence: 99%
See 3 more Smart Citations